Job characteristics as antecedents of intention to stay and mediating effects of work family facilitation and family satisfaction among single mothers in Malaysia - Noraani Mustapha; Aminah Ahmad; Jegak Uli; Khairuddin Idris (2010)
Employee turnover is crucial to be investigated since it diminishes organization effectiveness and impedes the capacity to meet its goals. This study was conducted to test the mediating effects of work-family facilitation and family satisfaction on the relationship between job characteristics, and intention to stay among 240 single mother employees in Malaysia. Data was collected using self-administered research questionnaire on simple randomized respondents whereby six out of 24 single mother associations were selected to obtain research samples. Descriptive statistical analysis was conducted to describe the respondents and Pearson Product Moment Correlation to determine the relationships among variables. Structural Equation Modeling using AMOS version 16.0 was utilized for model testing and to check the presence of mediation effects in the relationships between independent and dependent variables. The Soble’s z-test was used to test whether the mediators carry the effect of the independent variables on the dependent variable. The findings indicated that single mothers have moderate levels of job characteristics in their lives, so as their levels of work-family facilitation, family satisfaction and intention to stay. There were positive and negative significant relationships among variables. The results also established the presence of mediation effects between the independent and dependent variables. Organizations may utilize work-family facilitation and family satisfaction as mechanisms to promote longer retention among employees.